Respuesta :
Answer:
L.H.S. = [tex]\frac{1}{cosx} -\frac{sinx}{cosx}sinx[/tex]
= [tex]\frac{1}{cosx} - \frac{sin^2x}{cosx}[/tex]
= [tex]\frac{1-sin^x}{cosx} = \frac{cos^2x}{cos x}[/tex]
= cos x = 1/secx
Step-by-step explanation:
Hey there!
Given;
sec x - tan x . sin x = 1/(sec x).
~ Taking LHS.
= sec x - tan x . sin x
= 1/(cos x) - (sin x/cos x) . sin x { Using formula sec x = 1/cos x and tan x = (sin x/cos x)}
~ Multiply (sin x) and (sin x).
[tex] = \frac{1 - { (\sin(x) )}^{2} }{ \cos(x) } [/tex]
~ Use formula 1-sin²x= cos²x
[tex] = \frac{ {cos}^{2} x}{ \cos(x) } [/tex]
~ Cancel cos x.
= cos x
= 1/sec x { cos x = 1/sec x}
→ RHS proved.
Hope it helps.....